Design, Emotion, and Color: Analysis Study of the Scientific Production in the International Color Association (AIC) Proceedings - Alves, Ana Laura [UNESP]; Marteli, Leticia Nardoni [UNESP]; Silva, Fernando Moreira da; Paschoarelli, Luis Carlos [UNESP]; Broega, A. C.; Cunha, J.; Carvalho, H.; Providencia, B. (Springer, 2023)
The tactile or visual interaction with a product can evoke different emotional experiences in a person. In this context, contemporary research in color attributes this variable a relevant role in human factors and in emotion-driven design. Related to this, this study provides a critical review of the scientific production of Design, Emotion, and Color, in the International Color Association (AIC) proceedings. Therefore, the proceedings of all AIC conferences were checked (n = 66), since the first conference in 1969. The data underwent a bibliometric analysis to understand the general characteristics of scientific production and next, a qualitative synthesis of the selected full papers. A total of one hundred and forty-four (n = 144) full papers were assessed for eligibility criteria and only eight (n = 8) studies were included in the final analysis. The results indicated a growth in the number of full papers concerning Design, Emotion, and Color, as well as a diversity of methods and research scopes. The body of knowledge found in this study can contribute to the theoretical investigation and arouse the interest of designers and practitioners for new advances on the topic investigated.
Keywords: Color; Emotion; Semantics; Human factors; Design; International Color Association